2001
DOI: 10.1016/s0035-9203(01)90329-3
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the pfmdr1, dhfr and dhps genes of Plasmodium falciparum are associated with in-vivo drug resistance in West Papua, Indonesia

Abstract: This study (conducted in 1996-99) examines the association of mutations in pfmdr1, dihydrofolate reductase (dhfr) and dihydropteroate synthase (dhps) genes of Plasmodium falciparum with in-vivo drug resistance in West Papua, Indonesia. Initially, 85 patients infected with P. falciparum were treated with chloroquine, of whom 21 were cleared of parasites, 49 had parasitaemias classified as RI, RII or RIII resistance and 1 patient had recrudescent parasitaemia. Fansidar (pyrimethamine-sulfadoxine) was the second-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
69
1
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 32 publications
5
69
1
1
Order By: Relevance
“…Studies that have tested different P. falciparum isolates from PNG for mefloquine resistance showed full in vitro susceptibility (Hombhanje, 1998). By contrast, other authors previously have shown a high frequency of pfmdr1 sequence polymorphisms, confirming that chloroquine selects for polymorphisms (Nagesha et al, 2001).…”
Section: Discussionsupporting
confidence: 52%
“…Studies that have tested different P. falciparum isolates from PNG for mefloquine resistance showed full in vitro susceptibility (Hombhanje, 1998). By contrast, other authors previously have shown a high frequency of pfmdr1 sequence polymorphisms, confirming that chloroquine selects for polymorphisms (Nagesha et al, 2001).…”
Section: Discussionsupporting
confidence: 52%
“…In previous studies in Irian Jaya and West Papua, N86Y was found to show a correlation with CQ-resistant P. falciparum parasites. 11,12 The mutation K76T in the pfcrt gene was found in all but one (47 of 48, 97.9%) of the isolates studied. A previous report showed that the K76T mutation showed a correlation with clinical resistance to CQ and as a molecular marker had a sensitivity of 93% and a specificity of 82%.…”
mentioning
confidence: 93%
“…14,15 Ten mutant genotypes for DHFR have been reported from a large number of field samples. 4,[16][17][18] Resistance to sulfonamide and sulfones has been shown to result from mutations within dihydropteroate synthetase (DHPS). 19,[20][21][22] The amino acid changes at four positions (Ser-436, Gly-437, Ala-581, and Ala-613) have been shown to confer resistance to sulfadoxine and also cross-resistance to sulfones and sulfonamides.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Distribution of mutations in the dhfr and dhps genes and their association with Fansidar resistance have been assessed in different geographic areas, and it has been found that a greater number of mutations in both dhfr and dhps is a good predictor of likely drug failure. 4,17,18,23 Vietnam has well-developed systems for malaria surveillance, with recent data showing that more than half the population lives in forests and mountainous areas where they may be at risk of malaria infection. Drug-resistant malaria has been an increasing problem in the last two decades, and although alternative drugs such as artemisinin and its derivatives have become widely used as first-line therapy for malaria, they have been associated with a high frequency of recrudescence.…”
Section: Introductionmentioning
confidence: 99%